Data Privacy Using Anonymization Method on Open Data - Lê Thị Minh Châu; Nguyễn Trần Thi Văn (Journal of Technical Education Science, 2024)
Open Data is a type of data shared between organizations, agencies, businesses, governments, etc. It is mainly used to serve community projects in many fields: health, environment, education, etc. Nowadays, countries around the world are following the trend of building smart cities and smart governments. They are applying Open Data in these projects and achieving many significant benefits. However, sharing data can lead to many problems. In recent studies, many authors have pointed out that besides the benefits that Open Data offers, there are also risks in terms of security, including revealing information of individuals, organizations, and businesses. Data security using anonymization methods such as k-anonymity or l-diversity has been researched and applied for many years. However, these methods are just mainly implemented and tested on traditional data sets of businesses and organizations, not the data on Open Data. Therefore, this topic will focus on understanding Open Data, data security methods based on anonymization mechanism, implementing some security methods based on anonymization mechanism on Open Data and analyzing and evaluating research results.